Courts as Monitoring Agents: The Case of China - Xiaoge Dong; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2020)
This paper shows that courts are not only a crucial part of the rule of law in the conventional sense but that they can also serve an important function in revealing information regarding the performance of lower level governments to the central government, and thereby improve their performance. After having developed a general argument in that vein, the recent reforms to the Chinese court system are partially interpreted as an attempt to make the courts monitoring agents of the central government. Based on primary data from more than 1,000 Chinese local courts, the argument is tested empirically and its hypotheses are largely confirmed.
Keywords: H11; H77; K40; N45; P21; P37; 340; Court system of China; court reforms; courts-as-information-providers; courts as monitoring agents